Investigation Of Zinc Oxide Quantum Dots Based Thin Films On Flexible Substrate For Perovskite Solar Cells - Sani, Muhammad (2023)
In this research, ZQDs is synthesized via a cost-effective and solution- processed precipitation technique at low temperature (60-150 o C). The as-prepared colloidal ZQDs solution was spin-coated onto flexible Polyethelene terephthalate (PET) and indium-doped tin oxide coated Polyethelene terephthalate (ITO/PET) substrates. Tuning the optical and electrical properties of ZQDs films through changing experimental parameters without any doping has been reported. The influence of film thickness and ZQDs solution concentration (ZQC) on the structural, surface, compositional, optical and electrical properties of the spin-coated thin films and their effects on the FPKSCs performance were investigated.